Investigation of the Proof Complexity Measures of Strongly Equal K-Tautologies in Some Proof Systems - Chubaryan, Anahit Artashes; Khamisyan, Artur; Petrosyan, Garik (Transactions on Engineering and Computing Sciences, 2019)
Here we generalize the notions of determinative conjunct and strongly equal tautologies formany-valued logic (MVL) and compare the proof complexity measures of strongly equal many-valued tautologies in some proof systems of MVL. It is proved that in some “weak” proof system the strongly equal many-valued tautologies have the same proof complexities, while in the “strong” proof systems the measures of proof complexities for strongly equal tautologies can essentially differ from each other.